Transformasi Moderasi Beragama Berbasis Digital 2024: Sebagai Bentuk Upaya Memfilter Konten Radikalisme dan Ekstremisme di Era Disrupsi: Transformasi Moderasi Beragama Berbasis Digital 2024: Sebagai Bentuk Upaya Memfilter Konten Radikalisme dan Ekstremisme di Era Disrupsi - Mandala, Ican; Witro, Doli; Juraidi, Juraidi (Jurnal Bimas Islam, 2024)
The problem of community disintegration is a challenge for pluralistic societies. The massive spread of the virus of radicalism and extremism among religious communities is a factor in the widespread phenomenon of community division. The virus has an impact on the birth of intolerant understanding patterns among people of diversity. So that people clash with each other in differences, even presenting actions to negate each other. Along with the development of digitalisation, the intolerance virus has spread in the realm of digital media. The doctrine of radicalism and extremism with the use of digital media is effective in reaching a wider community, especially the younger generation. Intolerant content indoctrinates digital media users into radical and extreme understanding in the life of diversity. The spread of divisive content wrapped in a convincing narrative makes it difficult for people to filter content on digital media. Thus, efforts to prevent the problem of disintegration of the ummah in 2024 require the transformation of religious moderation by utilising digital space. This article analyses using the library research method, by conducting a literature review of books, scientific articles, magazines, websites and others. This article aims to explore the concept of realising the transformation of digital-based religious moderation based on the Qur'an which offers a concept in an effort to filter the content of radicalism and extremism. Based on in-depth analysis, the concept of realising the transformation of religious moderation in 2024 can be done by; 1). Understanding the diversity inclusiveness paradigm; 2). Exploration of content validity; 3). Understanding universal communication ethics; 4). Pro moderate narrative; 5). Millennials as moderate ambassadors.